Chronic Wound Telemedicine Models Before and During the COVID-19 Pandemic: A Scoping Review. (February 2022) - Kim, Patrick Jinhyung; Homsi, Haya A.; Sachdeva, Muskaan; Mufti, Asfandyar; Sibbald, R. Gary
Abstract : GENERAL PURPOSE: To present the results of a scoping review exploring chronic wound care telemedicine before and during the pandemic, including the characteristics of the models implemented. TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant will: 1. Identify the characteristics of the studies the authors examined for their scoping review of chronic wound care telemedicine. 2. Choose the electronic methods commonly used for wound care telemedicine in the studies the authors examined. 3. Recognize the implications for the patients who participated in chronic wound care telemedicine in the studies the authors examined. ABSTRACT: OBJECTIVE To explore different chronic wound telemedicine models and identify current research on this topic. METHODS The authors searched the MEDLINE and EMBASE databases on August 10, 2021 and identified 58 articles included in the analysis. RESULTS Included studies were published between 1999 and 2021, with more than half of the studies published between 2015 to 2019 (25.9%, n = 15/58) and 2020 to 2021 (25.9%, n = 15/58). There were 57 models identified, of which 87.7% (n = 50/57) used a blended model of care. Image assessment was the most common element in blended care (66.0%, n = 33/50), followed by video consultation (46.0%, n = 23/50), text (44.0%, n = 22/50), and telephone consultation (22.0%, n = 11/50). Purely virtual care was used in 12.3% (n = 7/57) of models, 85.7% (n = 6/7) of which were implemented during the COVID-19 pandemic. Most studies conducted a quantitative analysis (62.1%, n = 36/58); 20.7% (n = 12/58) conducted a qualitative analysis, and 17.2% (n = 10/58) conducted both. The most frequently assessed results were wound outcomes (53.4%, n = 31/58) and patient opinions (25.9%, n = 15/58). CONCLUSIONS Chronic wound care-related telemedicine has common elements: image assessment, video and telephone consultation, and text-based information that can be combined in a variety of ways with unique implementation barriers. Blended care models are more common than purely virtual alternatives. Heterogeneity among outcomes and reporting methods make the results difficult to synthesize. Abstract : Supplemental digital content is available in the text.